Inorganic water-permeable floor material composition

By using silicate cement, aggregate, blast furnace iron slag, water glass and degradable hydrogel particles in permeable floor materials, the problem of insufficient strength and permeability of existing permeable floor materials is solved. High water permeability and high compressive strength are achieved, and the service life is extended, avoiding the formaldehyde emission and strength reduction problems of organic adhesives.

CN119306463APending Publication Date: 2025-01-14SHANDONG KEHONG NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411572256.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing permeable floor materials have a lower strength due to the high feeding ratio of coarse aggregate and cement. The added organic adhesive will release formaldehyde during use, which will harm human health and fail under rainwater erosion, resulting in Floor strength is reduced and damaged.

Method used

The composition is adopted to adopt 20 to 50 parts of silicate cement, 40 to 80 parts of aggregate, 15 to 25 parts of blast furnace iron sludge, 4 to 10 parts of water glass and 3 to 8 parts of degradable absorbable hydrogel particles. The mass ratio of silicate cement is 1~2:1. The water permeability and strength of the floor are improved by blast furnace iron sludge and degradable hydrogel particles. Water glass is used as an exciter to promote hydration, and Free radical polymerization prepares efficient degradable and absorbable hydrogel particles.

Benefits of technology

It achieves high water permeability and high compressive strength of the floor, while extending the service life, avoiding the formaldehyde release and strength reduction of organic adhesives.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses an inorganic water-permeable terrace material composition, and relates to the technical field of concrete. The composition is prepared from the following components in parts by mass: Portland cement, aggregate, blast furnace iron smelting slag, water glass and degradable water-absorbing gel particles, the degradable water-absorbing gel particles are prepared by the following steps: adding a monomer into water, dissolving, adding an initiator and a degradable cross-linking agent, carrying out free radical polymerization, and after the polymerization is finished, crushing, drying and crushing to obtain the degradable water-absorbing gel particles. The inorganic permeable floor material composition disclosed by the invention has relatively high permeable rate and relatively high compressive strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete, and in particular to an inorganic permeable floor material composition. Background Art

[0002] With the development of my country's economy, the expansion of urban scale and changes in structure, the urban surface has gradually been covered by reinforced concrete houses, large-scale infrastructure, various impermeable sites and concrete pavements with extremely poor permeability. The proportion of concrete pavements is increasing, which has had many negative impacts on the social and ecological environment, especially urban waterlogging, groundwater level decline, heat island effect and other problems are becoming increasingly prominent.

[0003] Permeable floor is a new environmentally friendly road material. Compared with traditional concrete pavement, its advantage is that it has better permeability. Therefore, it can conduct rainwater and heat on the road surface to the underground, thus solving a series of problems of conventional concrete pavement. However, in the existing permeable floor, in order to ensure that the floor has a higher porosity and permeability coefficient, more coarse aggregate is usually added. The mass ratio of coarse aggregate to cement is usually above 3:1, and even some permeable floors can reach a mass ratio of 5:1 or more. The reduction of cementitious materials will reduce the strength of the permeable floor. Therefore, existing technicians usually add some organic adhesives. These adhesives will release formaldehyde during use, which is harmful to the health of pedestrians and workers. At the same time, these adhesives will gradually fail under the erosion of rainwater, especially in summer and autumn when there is more rain, which will cause the adhesive to fail, thereby reducing the strength of the floor and then causing damage. Summary of the invention

[0004] In view of the above technical problems, the purpose of the present invention is to provide an inorganic permeable floor material composition to address the defects of the prior art.

[0005] The present invention adopts the following technical scheme: an inorganic permeable floor material composition, calculated by weight, includes: 20-50 parts of silicate cement, 40-80 parts of aggregate, 15-25 parts of blast furnace iron smelting slag, 4-10 parts of water glass, and 3-8 parts of degradable water-absorbing gel particles, wherein the mass ratio of the aggregate to the silicate cement is 1-2:1; The degradable water-absorbing gel particles are prepared by the following method: adding monomers into water and dissolving them, adding initiators and degradable cross-linking agents to carry out free radical polymerization, and after the polymerization is completed, crushing, drying and pulverizing the monomers to obtain the degradable water-absorbing gel particles; the monomers include acrylic acid and acrylamide, and the amount of the degradable cross-linking agent added is 0.05-0.3% of the total mass of the monomers.

[0006] In the present invention, silicate cement and aggregate are similar to conventional permeable floors, but the difference from conventional floors is that in the present invention, the amount of aggregate added is lower, so the final floor has higher strength than conventional floor materials. At the same time, due to the lower amount of aggregate added, it will cause the water permeability of the floor to deteriorate. In order to solve this problem, blast furnace iron smelting slag and degradable water-absorbing gel are added in the present invention.

[0007] As for blast furnace iron smelting slag, it itself is a relatively weak cementitious material, which can enhance the strength of the floor to a certain extent; at the same time, blast furnace iron smelting slag within a certain size range, when it is hydrated and gelled, will form a large number of pores to enhance the water permeability of the floor. Theoretically speaking, blast furnace iron smelting slag with a particle size of 1~8mm can be applied to the present invention, but from the actual application effect, its particle size is preferably 2~5mm.

[0008] For blast furnace iron smelting slag, it usually requires a certain amount of activator to be able to hydrate faster. Existing activators include carbonates, flake caustic soda and water glass. After experiments, the inventor found that although carbonates can promote the hydration of blast furnace iron smelting slag, they have a negative impact on the strength of the floor, while water glass not only has a good promoting effect, but also has an enhancing effect on the strength of the floor.

[0009] For degradable water-absorbing gel particles, it specifically refers to: a gel that has certain water absorption and swelling properties and degrades under certain conditions after water absorption and swelling. There are many such gels in the prior art, but they are all difficult to be directly applied to the present invention. This is mainly because, although the existing degradable water-absorbing gel particles can be automatically degraded, their degradation speed is relatively slow, usually in a few days to dozens of days, and most of them need to be degraded under certain temperature conditions, which are difficult to be applied to the present invention. For this reason, the present invention proposes a new degradable water-absorbing gel particle, which is different from conventional water-absorbing gel particles in that the amount of degradable crosslinking agent added is relatively low, only 0.05-0.3% of the total weight of the monomer. Under such conditions, the obtained degradable water-absorbing gel particles have a higher water absorption and swelling multiple, a shorter degradation time, and are relatively close to the hardening time of the floor, so the strength of the floor will not be reduced due to its degradation.

[0010] In particular, for degradable water-absorbing gel particles, the monomers can be selected from conventional acrylic acid and acrylamide, which are common monomers in the art. Although other monomers, such as allyl sulfonate, etc., can also be selected, the cost of these monomers is relatively high. In order to maintain lower costs, one or two of acrylic acid and acrylamide can be selected. For the initiator of the degradable water-absorbing gel particles, it can use an initiator commonly used in free radical polymerization, such as a conventional persulfate initiator, a water-soluble redox initiator, etc., and the amount of the initiator added is 0.8~2wt% of the total mass of the monomer. It is known to those skilled in the art that for different initiators, the initiation temperature is different, so the reaction temperature also has a certain difference, such as ammonium persulfate initiator, the reaction temperature is usually 55~70°C, and the reaction time is usually 2~4h; for redox initiators, the reaction temperature can be set to room temperature, and the reaction time is 1~4h. Of course, those skilled in the art can also use other initiators that can be applied to the free radical polymerization of the present invention, and set a suitable reaction temperature and reaction time according to the selected initiator.

[0011] For the preparation process of degradable water-absorbing gel, theoretically, there is no need to care about the concentration of monomers. However, from the perspective of practical application, the inventors found that although the monomers can also react to generate corresponding gels under low and high concentration conditions, at low concentrations, the gel molding is difficult, which is not conducive to subsequent operations such as crushing; at high concentrations, the reaction is more violent, and the performance of the gel will also deteriorate. Therefore, after a large number of experiments, the inventors found that when the concentration of the monomer in water is 20-30wt%, the gel finally obtained has better performance, not only will not have a negative impact on the strength of the floor, but also make the water permeability of the floor better. At the same time, those skilled in the art can know that for the free radical polymerization described in the present invention, an inert gas needs to be introduced before the reaction to remove oxygen in the water. These belong to conventional operations in the art, so they are not described in detail.

[0012] One embodiment of the present invention is that the composition further comprises 1 to 3 parts of sodium hydroxide, which can not only promote the hydration of blast furnace iron smelting slag, but also accelerate the degradation of degradable water-absorbing gel particles, so that the floor has better water permeability.

[0013] One embodiment of the present invention is that the composition includes 35-40 parts of Portland cement, 55-70 parts of aggregate, 18-22 parts of blast furnace iron smelting slag, 6-7 parts of water glass, and 6-7 parts of degradable water-absorbing gel particles, and the mass ratio of the aggregate to the Portland cement is 1.5-1.8: 1. Under this condition, the water permeability of the floor is higher and the strength is higher.

[0014] An implementation manner of the present invention is that the aggregate is at least one of crushed stone and high-strength ceramsite, and the particle size of the aggregate is 3-8 mm.

[0015] One embodiment of the present invention is that the degradable water-absorbing gel particles are added with water to absorb water for 20 to 60 minutes before use. The degradable water-absorbing gel particles of the present invention have a large water absorption multiple. They can absorb water for 20 to 60 minutes before use, and can expand rapidly and approach the maximum expansion multiple, which can effectively reduce the problem of slow hydration of floor materials due to water absorption during the expansion process of the water-absorbing gel particles.

[0016] One embodiment of the present invention is that the degradable cross-linking agent is one of polyethylene glycol diacrylate, ethylene glycol dimethacrylate, and dipropylene glycol diacrylate, and the molecular weight of the polyethylene glycol diacrylate is 500 to 1500. These are common degradable cross-linking agents.

[0017] One embodiment of the present invention is that the composition further comprises 1 to 3 parts of a polycarboxylate water reducer. The water reducer is a common additive in the art, and in fact, such as an early strength agent, an accelerated setting agent, etc., can be applied to the present invention.

[0018] The beneficial effects of the present invention are: the inorganic permeable floor material composition of the present invention has higher water permeability and higher compressive strength, and has a longer service life. DETAILED DESCRIPTION

[0019] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical scheme of the present invention is described in detail below in conjunction with embodiments, but it should not be construed as limiting the applicable scope of the present invention.

[0020] In the following embodiments, unless otherwise specified, the operations described are routine operations in the art.

[0021] In the following examples, unless otherwise specified, all raw materials used are conventional commercial products in the art.

[0022] In the following examples, unless otherwise specified, the parts are by mass.

[0023] Example 1: Preparation of degradable water-absorbing gel particles: 150 parts of acrylic acid and 70 parts of acrylamide were dissolved in 800 parts of water, heated to 65°C under nitrogen deoxygenation conditions, 2.5 parts of ammonium persulfate and 0.26 parts of dipropylene glycol diacrylate were added, and the reaction was carried out for 2 hours. After the reaction, the gel was crushed, dried, pulverized and sieved to obtain the final degradable water-absorbing gel particles KJJ-1, whose size was 0.38~1.7 mm.

[0024] The floor composition includes 38 parts of silicate cement with a grade of 42.5, 65 parts of crushed stone aggregate with a particle size of 3-8 mm, 20 parts of blast furnace iron slag with a particle size of 2-5 mm, 6 parts of water glass, 7 parts of degradable water-absorbing gel particles KJJ-1, 2 parts of sodium hydroxide, and 2 parts of polycarboxylic acid water-reducing agent; wherein, before use, add sufficient water to the degradable water-absorbing gel particles KJJ-1 to allow it to absorb water for 40 minutes, and after absorbing water, filter out the degradable water-absorbing gel particles KJJ-1.

[0025] Example 2: Preparation of degradable water-absorbent gel particles: 280 parts of acrylic acid were dissolved in 800 parts of water, and the temperature was raised to 65° C. under nitrogen deoxygenation conditions. 2.5 parts of ammonium persulfate and 0.67 parts of polyethylene glycol diacrylate (molecular weight 1000) were added, and the reaction was carried out for 2 hours. After the reaction, the gel was crushed, dried, pulverized and sieved to obtain the final degradable water-absorbent gel particles KJJ-2, whose size was 0.38~1.7 mm.

[0026] The floor composition includes 24 parts of silicate cement with a label of 42.5, 45 parts of crushed stone aggregate with a particle size of 3-8 mm, 16 parts of blast furnace iron slag with a particle size of 2-5 mm, 6 parts of water glass, 7 parts of degradable water-absorbing gel particles KJJ-2, 2 parts of sodium hydroxide, and 2 parts of polycarboxylic acid water-reducing agent; wherein, before use, add sufficient water to the degradable water-absorbing gel particles KJJ-2 to allow it to absorb water for 40 minutes, and after absorbing water, filter out the degradable water-absorbing gel particles KJJ-2.

[0027] Example 3: Preparation of degradable water-absorbent gel particles: 150 parts of acrylic acid and 70 parts of acrylamide were dissolved in 800 parts of water. Under nitrogen deoxygenation and room temperature conditions, 2 parts of redox initiator (sodium persulfate and sodium bisulfite in a mass ratio of 1:1) and 0.67 parts of polyethylene glycol diacrylate (molecular weight 1000) were added, and the mixture was reacted for 2 hours. After the reaction, the gel was crushed, dried, pulverized and sieved to obtain the finally obtained degradable water-absorbent gel particles KJJ-3, whose size was 0.38~1.7 mm.

[0028] The floor composition includes 45 parts of silicate cement with a label of 42.5, 75 parts of crushed stone aggregate with a particle size of 3-8 mm, 24 parts of blast furnace iron slag with a particle size of 2-5 mm, 8 parts of water glass, and 5 parts of degradable water-absorbing gel particles KJJ-3; wherein, sufficient water is added to the degradable water-absorbing gel particles KJJ-3 before use to allow it to absorb water for 40 minutes, and the degradable water-absorbing gel particles KJJ-3 can be filtered out after absorbing water.

[0029] Example 4: Preparation of degradable water-absorbing gel particles: the same as Example 1.

[0030] Floor composition: Compared with Example 1, the difference is that the degradable water-absorbing gel particles are directly mixed with other materials when used.

[0031] Example 5: Preparation of degradable water-absorbing gel particles: the same as Example 1.

[0032] Floor composition: Compared with Example 1, the difference is that the particle size of blast furnace iron smelting slag is 1~3mm, and the rest is the same.

[0033] Example 6: Preparation of degradable water-absorbing gel particles: the same as Example 1.

[0034] Floor composition: Compared with Example 1, the difference is that the particle size of blast furnace iron smelting slag is 5~8mm, and the rest is the same.

[0035] Example 7: Preparation of degradable water-absorbing gel particles: Compared with Example 1, the difference is that acrylic acid and acrylamide are added to 500 parts of water, and the rest are the same.

[0036] Floor composition: the same as in Example 1.

[0037] Comparative Example 1 Preparation of degradable water-absorbing gel particles: the same as in Example 1.

[0038] Floor composition: Compared with Example 1, the difference is that the amount of crushed stone aggregate added is 82 parts, and the rest are the same.

[0039] Comparative Example 2 Preparation of degradable water-absorbing gel particles: Compared with Example 1, the difference is that the amount of dipropylene glycol diacrylate added is 2.2 parts, and the rest is the same.

[0040] Floor composition: the same as in Example 1.

[0041] Comparative Example 3 No degradable water-absorbing gel particles were added, and the rest were the same.

[0042] Floor composition: the same as in Example 1.

[0043] In order to further illustrate the advantages of the embodiments of the present invention, they are described below in conjunction with specific experimental data.

[0044] 1. Water permeability test The floor compositions of Examples 1 to 7 and Comparative Examples 1 to 2 were added with water to prepare concrete floors, which were then cured at room temperature. The water permeability coefficients were measured at intervals. The final results are shown in Table 1. The unit of the water permeability coefficient is mm / s. During the curing process, water was sprayed at intervals of 10 days, and the water spraying rate was 10 mm / cm 3, to simulate the rainfall process in nature. The test method of water permeability coefficient refers to the method disclosed in GB / T25993-2010 "Permeable Pavement Bricks and Permeable Road Panels". Among them, the water-cement ratio of the floor composition of Examples 1 to 3, 5 to 7 and Comparative Examples 1 to 2 is 0.28, and the water-cement ratio of Example 4 is 0.5 (taking into account the water absorption of the degradable water-absorbing gel particles themselves); when preparing the concrete floor, mix the composition, then add the corresponding water and stir evenly, and then cure and shape it.

[0045] Table 1 Water permeability test results

[0046] It can be seen from comparative document 1 that the floor composition of the embodiment of the present invention has high water permeability after being made into a floor. In comparative example 2, the water permeability after curing for 90 days is relatively high, which may be due to the large amount of cross-linking agent added to the degradable water-absorbing gel particles, resulting in a lower expansion multiple and a slower degradation rate.

[0047] 2. Compressive strength test Referring to GB / T50081-2002 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete", add water to the floor compositions of Examples 1 to 7 and Comparative Examples 1 to 2 to prepare at least 3 groups of concrete floors, then cure them at room temperature for a period of time and measure their compressive strength. During the curing process, spray water every 10 days at a spray rate of 10 mm / cm 3 , to simulate the rainfall process in nature; after curing for 28 days, apply force to the concrete floor twice every 5 days, with a single action time of 5 seconds and a magnitude of 2MPa, to simulate the force applied to the floor during the driving of a small family car. Among them, the water-cement ratio of the floor composition of Examples 1 to 3, 5 to 7 and Comparative Examples 1 to 2 is 0.28, and the water-cement ratio of Example 4 is 0.5 (taking into account the water absorption of the degradable water-absorbing gel particles themselves); when preparing the concrete floor, mix the composition, then add the corresponding water and stir evenly, and then cure it to form.

[0048] Table 2 Compressive strength test table

[0049] In Table 2, “——” indicates that the concrete floor is damaged.

[0050] It can be seen from Table 2 that the inorganic permeable floor material composition of the embodiment of the present invention has relatively high strength.

[0051] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the embodiments of the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. An inorganic permeable floor material composition, characterized in that: The composition comprises, by weight: 20 to 50 parts of Portland cement, 40 to 80 parts of aggregate, 15 to 25 parts of blast furnace iron smelting slag, 4 to 10 parts of water glass, and 3 to 8 parts of degradable water-absorbing gel particles, wherein the mass ratio of the aggregate to the Portland cement is 1 to 2:1; The degradable water-absorbing gel particles are prepared by the following method: adding monomers into water and dissolving them, adding initiators and degradable cross-linking agents to carry out free radical polymerization, and after the polymerization is completed, crushing, drying and pulverizing the monomers to obtain the degradable water-absorbing gel particles; the monomers include acrylic acid and acrylamide, and the amount of the degradable cross-linking agent added is 0.05-0.3% of the total mass of the monomers.

2. The composition according to claim 1, characterized in that The composition also includes 1 to 3 parts of sodium hydroxide.

3. The composition according to claim 1, characterized in that The composition comprises 35-40 parts of silicate cement, 55-70 parts of aggregate, 18-22 parts of blast furnace iron smelting slag, 6-7 parts of water glass, and 6-7 parts of degradable water-absorbing gel particles, and the mass ratio of the aggregate to the silicate cement is 1.5-1.8:

1.

4. The composition according to claim 1, characterized in that The aggregate is at least one of crushed stone and high-strength ceramsite, and the particle size of the aggregate is 3-8 mm.

5. The composition according to claim 1, characterized in that The particle size of the blast furnace iron smelting slag is 2-5 mm.

6. The composition according to claim 1, characterized in that During the preparation of the degradable water-absorbing gel particles, the concentration of the monomer in water is 20-30 wt %.

7. The composition according to claim 1, characterized in that In the preparation process of the degradable water-absorbing gel particles, the initiator is one of a persulfate initiator and a water-soluble oxidation / reduction initiator, and the amount of the initiator added is 0.8-2wt% of the total weight of the monomer.

8. The composition according to claim 1, characterized in that Before use, the degradable water-absorbing gel particles are added with water to allow them to absorb water for 20 to 60 minutes.

9. The composition according to claim 1, characterized in that The degradable cross-linking agent is one of polyethylene glycol diacrylate, ethylene glycol dimethacrylate and dipropylene glycol diacrylate, and the molecular weight of the polyethylene glycol diacrylate is 500-1500.

10. The composition according to claim 1, characterized in that The composition also includes 1 to 3 parts of a polycarboxylate water reducer.